Using tethers to build a “capture portal” for the planets - Ferreira, A. F.S. (2018)
Several new applications of space tethers to maneuver spacecrafts have been suggested recently. Some of them are combinations with the sling shot effect used in several interplanetary missions. In one type of this family of applications, the tether is attached to an asteroid to make a rotation of the spacecraft, so giving energy to send it to the exterior planets of the Solar System or beyond. A similar idea is to make the capture of spacecrafts by a planet of the Solar System using tethers fixed on their moons. In both of these proposals, the tether is carried on-board the spacecraft and anchored to the celestial body during the approach phase. Another possibility is to build an Escape Portal using a tether permanently fixed in an asteroid to give energy to spacecrafts to go to the outer planets. The present paper explores in more detail a combination of those two proposals to build a Capture Portal for the planets. The main idea is to build a permanent structure fixed on one of the moons of a given planet, so that it can be used for an unlimited number of maneuvers. With this goal, this research searches for equilibrium points that can be used to place the above structures. The type of force in the tether and the stability of the points are also considered. The results shown here can give some insights in the problems that appear when building such “Capture Portal”.